The rise of ordinary stars in cyberspace - New Sunday, Times (NST, 2014)
Just a few years ago, only the ideas of politicians, academics and mainstream 'opinion leaders' dominated national discussion. Social media,however, has revolutionised that. Now, ordinary people can share their thoughts on social media platforms and,more interestingly, some are getting more followers than celebrities, writes Arman Ahmad